Analisis finaciero de la empresa grupo internet para todos sucursal Babahoyo - Burgos Chavez, Livington Moises (2019)
It has a low profitability, so it is necessary to examine and evaluate the strategies and the financial approach, you can make a report that improves your profitability, could verify that it is a company that has come in growth, without presenting a financial risk greater, although it is also reflected in the different tables shown, that the utility of the company does not present a significant increase, evolution of the financial statements of the Company Grupo Internet Para Todos, in which you can see the absolute and relative variation that is Produced between 2017 and 2018. The profitability shown by the company is positive, but it should improve, since it does not reach 20%, which implies an impediment to the optimal development of the company